Provocările actuale privind exercitarea mandatului Avocatului Poporului în contextul angajamentelor de asociere - Zubco, Alexandru (CEP USM, 2024)
On July 1, 2016, the Association Agreement between the European Union and the European Atomic Energy Community and their member states and the Republic of Moldova entered into force. And, on August 4, 2017, the Association Council approved the EU-Republic of Moldova Association Program. Among the short-term priorities of the program in the field of "political dialogue, good governance and strengthening institutions" was, inter alia, the completion of the reform of the People's Advocate institution, by improving Law no. 52 of April 3, 2014 regarding the People's Advocate (Ombudsman), in in accordance with the recommendations of the Venice Commission, and ensuring its financing according to the Paris Principles. In concrete terms, according to the Association Program, the Government of the Republic of Moldova was to strengthen the function of the People's Advocate, including through amendments to the law on the People's Advocate and the law on whistleblowers, by providing human and financial resources and an appropriate headquarters , in accordance with the provisions of the National Human Rights Action Plan, so that the Ombudsman can carry out his duties effectively. In 2023, the Parliament of the Republic of Moldova adopts urgent amendments to the Law on the People's Advocate, which aims at the inviolability of the Ombudsman, the procedure for appointing the People's Advocate, the conditions for early termination of the mandate, the exclusion of the public competition for the Ombudsman's deputies and the imposition of the duty to pay stamp duties in the case of actions in court. These changes were presented to the Association Council in 2023. Then, through the European Commission's 2023 country report, it is mentioned that the institution of the Ombudsman has been fully consolidated; the institution has "A" status; such as that the Ombudsmen enjoy inviolability when carrying out their duties and that the revocation of both lawyers requires a prior hearing by the full Parliament. At the same time, the European document suggests that the office is financed from the state budget, and its representatives have the right to address the parliament if the resources made available are insufficient to fulfill their mandate. Following the 2023 Expansion Package, it was decided to grant the EU candidate status to the Republic of Moldova. On June 21, 2024, the decree on the initiation of accession negotiations was signed. The respective article shows certain aspects omitted during the period of strengthening the capacities of the Ombudsman Institution, as well as some problematic aspects in achieving the full constitutional mandate of the People's Advocate in the context of European association commitments. The paper shows the importance of implementing the recommendations of the Association Council, of the Venice Commission, of the Universal Periodic Review tool by national authorities in order to have an independent and consolidated institution for a real protection of fundamental rights and freedoms.

La 01 iulie 2016 a intrat în vigoare Acordul de asociere între Uniunea Europeană și Comunitatea europeană a energiei atomice și statele membre ale acestora și Republica Moldova29. Iar, la 4 august 2017, Consiliul de asociere a aprobat Programul de asociere UE-Republica Moldova. Printre prioritățile pe termen scurt ale programului pe domeniul „dialog politic, bună guvernanță și consolidarea instituțiilor” a fost inter alia, finalizarea reformei instituției Avocatului Poporului, prin îmbunătățirea Legii nr.52 din 3 aprilie 2014 cu privire la Avocatul Poporului (Ombudsmanul), în conformitate cu recomandările Comisiei de la Veneția, și asigurarea finanțării acesteia conform Principiilor de la Paris30. In concreto, potrivit Programului de asociere, Guvernul R. Moldova urma să consolideze funcția de Avocat al Poporului, inclusiv prin modificări aduse legii privind Avocatul Poporului și legii privind avertizorii de integritate, prin punerea la dispoziție a resurselor umane și financiare și a unui sediu adecvat, în conformitate cu dispozițiile din Planul național de acțiune pentru drepturile omului, pentru ca Avocatul Poporului să își poată îndeplini sarcinile în mod eficace. În 2023, Parlamentul R. Moldova, adoptă modificări urgente la Legea cu privire la Avocatul Poporului ce vizează inviolabilitatea Ombudsmanului, procedura numirii Avocatului Poporului, condițiile încetării înainte de termen a mandatului, excluderea concursului public pentru adjuncții Ombudsmanului și impunerea sarcinii achitării taxelor de timbru în cazul acțiunilor în instanța de judecată. Aceste modificări au fost prezentate Consiliului de asociere în 2023. Urmare, prin raportul de țară al Comisiei europene din 2023, se menționează că instituția Ombudsmanului a fost consolidată complet; instituția dispune de statutul „A”; precum că Ombudsmanii se bucură de inviolabilitate atunci când își îndeplinesc sarcinile și că revocarea ambilor avocați presupune o audiere prealabilă de către plenul Parlamentului. Concomitent, documentul european sugereaz că oficiul este finanțat de la bugetul de stat, iar reprezentanții săi au dreptul de a se adresa parlamentului în cazul în care resursele puse la dispoziție sunt insuficiente pentru a-și îndeplini mandatul31. În urma Pachetului de extindere 2023, a fost decisă acordarea statutului de candidat la UE Republicii Moldova. La 21 iunie 2024 a fost semnat decretul privind inițierea negocierilor de aderare32. Articolul respectiv arată anumite aspecte omise în perioada de fortificare a capacităților Instituției Ombudsmanului, cât și unele aspecte problematice în realizarea mandatului constituțional deplin al Avocatului Poporului în contextul angajamentelor de asociere europeană. Lucrarea arată asupra importanței implementării recomandărilor Consiliului de asociere, a Comisiei de la Veneția, a instrumentului Evaluării Universale Periodice de autoritățile naționale pentru a avea o instituție independentă și consolidată pentru o protecție reală a drepturilor și libertăților fundamentale.
Currentchallenges regarding the exercise of the mandate of the people's advocate in the context of association commitments
Keywords: the People's Advocate; Ombudsman; international human rights standards; human rights; democracy; obligations of public authorities; Office of the People's Advocate; independence; impartiality; interference; European Union; Government; Decree; Venice Commission; Paris Principles; Avocatul Poporului; Ombudsmanul; standarde internaționale privind drepturile omului; drepturile omului; democrație; obligațiile autorităților publice; Oficiul Avocatului Poporului; independență; imparțialitate; imixtiune; uniunea europeană; guvern; decret; Comisia de la Veneția; Principiile de la Paris